Optimization of Liquid Soap Preparation Formula with the Addition of Black Rice (Oryza Sativa L. Indica) Extract as Anti-Radical Free based Virgin Coconut Oil (VCO) - Imamsyah, Ragil Agnes Safira; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2022)
An imbalance in the body's number of antioxidants and free radicals can cause oxidative stress and trigger various degenerative diseases (WHO, 2016). One way to prevent free radicals from entering the body is to bathe with soap. Black rice extract can be an antioxidant in soap because it contains anthocyanin pigments and has high bioactive compounds (Chakuton et al., 2012). Selection of Virgin Coconut Oil (VCO) as a raw material for soap because it has a high lauric acid content and is helpful for moisturizing and smoothing the skin (Afrozi et al., 2021). This study aimed to analyze the quality of liquid soap from the hydrolyzed Virgin Coconut Oil (VCO) and the effect of using bases KOH, NH4OH, and black rice extract accompanied by varying base concentrations, time, and temperature treatments. The independent variables for process optimization were the concentration of KOH: NH4OH (30:70, 50:50, 70:30)%, stirring time (65, 85, 105) minutes, and operating temperature (60, 75, 90) °C. Based on the results obtained, the optimum level of FFA (resulting in a small FFA%) was obtained with the minimized variable conditions, namely using a concentration of 16,4% KOH, and an operating temperature of 49,7 °C, a stirring time of 51.4 minutes, and composite desirability of 0,895897.